Penanganan Kecanduan Game Online Pada Mahasiswa Tingkat Akhir (Studi Kasus) - Anggia Wahyu Agustin; Yeni Karneli (Indonesian Journal of Counseling and Development, 2022)
Gaming addiction is the intense and excessive use of games which can lead to various problems. Individuals spend time playing online games, there will be disturbances especially in their study, social, school, and work life. The purpose of this study was to describe the causes of online games addiction in students. This research was carried out using a case study method with 1 respondent. The results of this study are addiction to this games has an impact on the completion of his final assignment as a student, his social relationships are disrupted because he becomes more individualistic. This activity is carried out through individual counseling services provided by counselors to clients